Insulin secretion, sensitivity, and clearance in normoglycemic Black and White adults with parental type 2 diabetes: association with incident dysglycemia - Samuel Dagogo-Jack; Jim Wan; Chimaroke Edeoga; Peace Asuzu (BMJ Open Diabetes Research & Care)
Introduction Ethnic disparities in the prevalence and pathophysiology of type 2 diabetes are well documented, but prospective data on insulin dynamics vis-à-vis pre-diabetes/early dysglycemia risk in diverse populations are scant.Research design and methods We analyzed insulin secretion, sensitivity, and clearance among participants in the Pathobiology of Prediabetes in a Biracial Cohort (POP-ABC) study. The POP-ABC study followed initially normoglycemic offspring of parents with type 2 diabetes for 5.5 years, the primary outcome being incident dysglycemia. Assessments included anthropometry, oral glucose tolerance test, insulin sensitivity (hyperinsulinemic euglycemic clamp, HEC), insulin secretion (intravenous glucose tolerance test, IVGT), and disposition index (DI). Insulin clearance was derived as the molar ratio of plasma C peptide to insulin and by calculating the metabolic clearance rate during HEC.Results POP-ABC participants who completed IVGT and HEC at baseline (145 African American, 123 European American; 72% women; mean age 44.6±10.1 years) were included in the present analysis. The baseline fasting plasma glucose was 91.9±6.91 mg/dL (5.11±0.38 mmol/L) and 2-hour plasma glucose was 123±25.1 mg/dL (6.83±1.83 mmol/L). African American offspring of parents with type 2 diabetes had higher insulin secretion and DI, and lower insulin sensitivity and clearance, than their European American counterparts. During 5.5 years of follow-up, 91 of 268 participants developed incident dysglycemia and 177 maintained normoglycemia. In Cox proportional hazards models, insulin secretion (HR 0.997 (95% CI 0.996 to 0.999), p=0.005), insulin sensitivity (HR 0.948 (95% CI 0.913 to 0.984), p=0.005), DI (HR 0.945 (95% CI 0.909 to 0.983), p=0.005) and basal insulin clearance (HR 1.030 (95% CI 1.005 to 1.056), p=0.018) significantly predicted incident dysglycemia.Conclusions Insulin sensitivity, secretion, and clearance differ significantly in normoglycemic African American versus European American offspring of parents with type 2 diabetes and are associated with the risk of incident dysglycemia.